1998
DOI: 10.1046/j.1365-294x.1998.00440.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene flow between insular, coastal and interior populations of brown bears in Alaska

Abstract: The brown bears of coastal Alaska have been recently regarded as comprising from one to three distinct genetic groups. We sampled brown bears from each of the regions for which hypotheses of genetic uniqueness have been made, including the bears of the Kodiak Archipelago and the bears of Admiralty, Baranof and Chichagof (ABC) Islands in southeast Alaska. These samples were analysed with a suite of nuclear microsatellite markers. The 'big brown bears' of coastal Alaska were found to be part of the continuous co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
224
6

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 298 publications
(241 citation statements)
references
References 31 publications
11
224
6
Order By: Relevance
“…Furthermore, the precise correspondence between geographic and phylogenetic divisions suggests three evolutionary significant units for conservation (9, 13) (clades II, III, and IV). In contrast, nuclear microsatellite data in Alaskan brown bears do not support long-term genetic isolation of the three Alaskan clades, suggesting the possibility of sex-biased dispersal (14).…”
mentioning
confidence: 65%
“…Furthermore, the precise correspondence between geographic and phylogenetic divisions suggests three evolutionary significant units for conservation (9, 13) (clades II, III, and IV). In contrast, nuclear microsatellite data in Alaskan brown bears do not support long-term genetic isolation of the three Alaskan clades, suggesting the possibility of sex-biased dispersal (14).…”
mentioning
confidence: 65%
“…This latter population is relatively large (42500) and healthy, with low genetic diversity attributed to a long period of isolation from the bears on the continent (Paetkau et al, 1998a(Paetkau et al, , 1998b. On the other hand, the demographic history of the other populations with low genetic diversity is presumed to be one of a recent contraction and isolation.…”
Section: Discussionmentioning
confidence: 98%
“…To study the likelihood of finding one of the observed autosomal genotypes in each one of the reference populations, we used an assignment test (Paetkau et al, 1995(Paetkau et al, , 1998Waser and Strobeck, 1998). This calculates the log likelihood of finding a certain genotype combination in each population and assigns the individual to the population for which it has the highest likelihood.…”
Section: Discussionmentioning
confidence: 99%